First Total Synthesis of a Naturally Occurring Iodinated 5′-Deoxyxylofuranosyl Marine Nucleoside - Jianyun Sun; Yanhui Dou; Haixin Ding; Ruchun Yang; Qi Sun; Qiang Xiao (Marine Drugs, 2012)
4-Amino-7-(5′-deoxy-β-d-xylofuranosyl)-5-iodo-pyrrolo[2,3-d]pyrimidine 1, an unusual naturally occurring marine nucleoside isolated from an ascidan, Diplosoma sp., was synthesized from d-xylose in seven steps with 28% overall yield on 10 g scale. The key step was Vorbrüggen glycosylation of 5-iodo-pyrrolo[2,3-d]pyrimidine with 5-deoxy-1, 2-O-diacetyl-3-O-benzoyl-d-xylofuranose. Its absolute configuration was confirmed.